2000
DOI: 10.1177/000331970005101104
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Results of Abciximab Versus Aspirin in Conjunction with Thrombolysis for Patients with Peripheral Occlusive Arterial Disease and Arterial Thrombosis

Abstract: Acute peripheral occlusive arterial disease is an important cause of morbidity and mortality, particularly among older persons. Catheter-directed thrombolytic therapy is the treatment of choice but has limitations: long lytic times, occlusions refractory to thrombolysis, and a high rate of restenosis. We conducted a pilot study to evaluate the use of the platelet GP IIb/IIIa receptor antagonist abciximab versus aspirin in conjunction with thrombolysis in patients with acute peripheral occlusive arterial diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…A small study by Schweizer et al [50] randomized 84 patients to 5 mg rt-PA intravenously and 500 IU heparin/hr along with either 500 mg aspirin or a bolus of 0.25 mg/kg abciximab followed by 10 g/min over 12 hr with 250 IU heparin/hr. Primary efficacy criteria included the number of rehospitalizations, reinterventions, and amputations during the following 6 months.…”
Section: Acute Critical Limb Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…A small study by Schweizer et al [50] randomized 84 patients to 5 mg rt-PA intravenously and 500 IU heparin/hr along with either 500 mg aspirin or a bolus of 0.25 mg/kg abciximab followed by 10 g/min over 12 hr with 250 IU heparin/hr. Primary efficacy criteria included the number of rehospitalizations, reinterventions, and amputations during the following 6 months.…”
Section: Acute Critical Limb Ischemiamentioning
confidence: 99%
“…Secondary peripheral occlusive arterial disease variables became highly significant vs. aspirin (P Ͻ 0.001 or greater) at 3 and 6 months after treatment. Thus, adjunctive use of abciximab reduced the rates of rehospitalization, reinterventions, and amputations vs. the results with the use of aspirin [50]. In the PROMPT trial [51], 70 patients with peripheral arterial occlusion of less than 6 weeks' duration were randomized to urokinase plus abciximab vs. urokinase plus placebo.…”
Section: Acute Critical Limb Ischemiamentioning
confidence: 99%
“…Although proof of a direct benefit for aspirin therapy in patients with intermittent claudication (IC) is lacking, 1,2 the increased cardiovascular morbidity and mortality in this patient group is widely regarded as a justification for antiplatelet therapy 3,4 . Aspirin treatment in patients with carotid artery disease is well established 5–7 . Meta‐analysis of randomized trials has shown a 25% reduction in vascular end‐points in patients at high risk of vascular complications and has indicated a 48% reduction in vascular graft and arterial occlusion 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Aspirin treatment in patients with carotid artery disease is well established. [5][6][7] Meta-analysis of randomized trials has shown a 25% reduction in vascular end-points in patients at high risk of vascular complications and has indicated a 48% reduction in vascular graft and arterial occlusion. 5,6 Reducing risk of recurrent vascular events is offset by a dose-dependent increased risk of bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…In a preliminary investigation it was demonstrated that after 6 months patients who receive abciximab benefited in terms of the rehospitalization rate and amputation rate compared to patients treated with aspirin alone. 4 The results raise the question as to whether other GP IIb/IIIa blockers also have this effect and whether treatment costs can be reduced. Effects similar to those described for abciximab in patients undergoing PTA have been described for other GP IIb/IIIa blockers in several cardiologic studies.…”
mentioning
confidence: 99%